Trends in Ear Traits of Chinese Maize Cultivars from the 1950s to the 2000s. (1st January 2013) - Ci, Xiaoke; Zhang, Degui; Li, Xinhai; Xu, Jiashun; Liang, Xiaoling; Lu, Zhenyu; Bai, Pengfei; Ru, Gaolin; Bai, Li; Hao, Zhuanfang; Weng, Jianfeng; Li, Mingshun; et al.
Abstract : Retrospective analyses of genetic yield may provide an understanding of unexploited genetic potential and indicate pathways for future yield improvement, and could be the basis of further study for exploiting molecular mechanisms of yield improvement in the future. The objective of this study is to further examine maize ( Zea mays L.) yield trends and describe changes in ear traits and the relationship between grain yield and ear traits from the 1950s to the 2000s in China. Trials were conducted at three locations in 2007 and 2008 and at five locations in 2009. Twenty‐seven single‐cross hybrids, four double‐cross hybrids, and four open‐pollinated varieties were grown at three densities at each location in each year. Grain yield potential per plant increased from 141.2 g for the 1950s' open pollination varieties (OPVs) to 306.5 g for the hybrids from the 2000s, and improved significantly from 1950 to 1970 and from 1990 to 2000. Overall, all ear traits tended to increase; however, the degree of improvement in ear traits varied among different eras and different traits. Advances in grain yield were attributable to kernel number per ear and kernel weight from the 1950s to 2000s in China. Kernel number per row, shelling percentage, and percentage barrenness need more improvement, and breeders in China should attempt to achieve gains for kernel number while maintaining kernel weight.